2005
DOI: 10.1002/rcm.2108
|View full text |Cite
|
Sign up to set email alerts
|

Determination of seven benzoylphenylurea insecticides in processed fruit and vegetables using high‐performance liquid chromatography/tandem mass spectrometry

Abstract: A liquid chromatographic method with electrospray ionization tandem mass spectrometry (LC/ESI-MS/MS) has been developed for the sensitive and selective determination of seven benzoylphenylurea insecticide residues (diflubenzuron, triflumuron, lufenuron, flufenoxuron, teflubenzuron, chlorfuazuron, hexaflumuron) in pear baby purée, concentrated lemon juice, and tomato pulp. The general sample extraction/partition method for our established multiresidue methods has been used. The entire procedure involves extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…Determination of CFZ by HPLC-MS/MS assay in processed fruits and vegetables was found to be more sensitive, with an LOQ of 0.001-0.02 µg/g but with recovery at only 69-88%. 24) However, the sensitivity in our study was better than or comparable to the reported detection of CFZ using GC-ECD in green tea samples with an LOD of 0.008-0.015 µg/g and recovery of 75-89%. 18) The developed GC-MS assay was also found to be more sensitive than the HPLC-DAD or UV assays using apple and pear specimens.…”
Section: Validation Test 41 Sensitivity and Recoverysupporting
confidence: 56%
See 1 more Smart Citation
“…Determination of CFZ by HPLC-MS/MS assay in processed fruits and vegetables was found to be more sensitive, with an LOQ of 0.001-0.02 µg/g but with recovery at only 69-88%. 24) However, the sensitivity in our study was better than or comparable to the reported detection of CFZ using GC-ECD in green tea samples with an LOD of 0.008-0.015 µg/g and recovery of 75-89%. 18) The developed GC-MS assay was also found to be more sensitive than the HPLC-DAD or UV assays using apple and pear specimens.…”
Section: Validation Test 41 Sensitivity and Recoverysupporting
confidence: 56%
“…Some of the published studies dealt with measurement of a single BPU, [13][14][15][16] whereas others involved measurements of residues of multiple BPUs. [17][18][19][20][21][22] Generally, analyses of BPUs have been accomplished by high performance liquid chromatography (HPLC) in combination with ultraviolet, 14) diode array detection (DAD), 23) mass spectrometry (MS), 13) and tandem mass spectrometry 24) detection systems. Alternative methods, such as gas chromatography (GC) coupled with electron-capture detection (ECD) 15) or mass spectrometry (MS), 16) have also been applied to screen BPUs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of sophisticated analytical methods which are capable of detecting trace quantities of pesticides has become increasingly important in the field of pesticide chemistry. Previous attempts have been made for analysis of BPU's residues by HPLC with fluorescent detector [6] and LC-MS [7,8]. Alternative methods such as ultraviolet (UV) determinations have also been used for the detection of BPU residues.…”
Section: Introductionmentioning
confidence: 99%
“…Zrostlikova et al (2003) determined the residues of diflubenzuron, triflumuron, teflubenzuron, flufenoxuron and 13 other polar/thermolabile pesticides in apples and apricots using ion trap MS/MS detection. Sannino and Bandini (2005) described a method based on LC/MS/MS with electrospray ionization (ESI) for the determination of seven BPUs in processed fruit and vegetables. The advantages of this detection, in addition to the increased analytical speed, lessen the cost per sample by reducing the solvent consumption.…”
Section: Introductionmentioning
confidence: 99%